Cyber-bystanders' reactions toward tourism companies' prejudice practice during the COVID-19 pandemic. (December 2021) - Liu, Jingyu; Long, Anna; Li, Minglong; Bai, Billy
Abstract: Prejudice against tourists from the epidemic areas or those infected during the COVID-19 pandemic has attracted much attention. While many studies examined the influence of this prejudice on tourists themselves, little research has been conducted to identify cyber-bystanders' reactions to tourism companies' prejudice practice. This study aims to fill this gap by revealing the process of how cyber-bystanders identify, evaluate, and respond online to prejudice practice in the context of the tourism industry. The study developed a conceptual model to examine the influential factors and their internal relationship of cyber-bystanders' reactions. A multistage model was proposed based on the social comparison theory. An online survey was conducted in mainland China, and 558 useable questionnaires were collected. The three-process model was estimated using the Bootstrap mediation test and hierarchical regression analysis. The results indicate that cyber-bystanders' prejudice recognizing process could impact their reactions through the influence of their evaluation behaviors. Meanwhile, the collective sentiment on social media has a moderating effect on the relationship between cyber-bystanders' evaluating process and their reactions to prejudice practice. Both theoretical and practical implications were discussed.